Novel Gene Mutations Associated with Crouzon Syndrome - D.Angel Fastina Mary (Indian Journal of Forensic Medicine & Toxicology, 2020)
Crouzon syndrome exhibits consideration of phenotypic heterogeneity, within the aetiology of whichgenetics play a crucial role. The FGFR2 gene mediates extracellular signals into cells and mutations withinthe FGFR2 gene cause Crouzon syndrome. The review summarizes the genetic phenotype study and geneticevaluation related to Crouzon syndrome (CS) which frequently determines the degree of complexity, guidemanagement, guidance and intervention related to this craniofacial defect. CS is a disorder characterizedby early fusion of certain skull bones (craniosynostosis). This prevents normal growth of the skull, whichmay affect the form of the top and face. Signs and symptoms of Crouzon syndrome may include wide-set,bulging eyes; strabismus (misalignment of the eyes); “beak-shaped” nose; and an underdeveloped upperjawbone. Other features may include dental problems, deafness, and/or harelip and palate. The severity ofsigns and symptoms can vary among affected people, even within a family. Intelligence is typically normal,but intellectual disability could also be present. Crouzon syndrome is caused by changes (mutations) withinthe FGFR2 gene and is inherited in an autosomal dominant manner. Treatment may involve surgeries to stopcomplications, improve function, and aid in healthy psychosocial development.